The study of characteristic behavior of prestressed beam at ultimate limit state / Che Adnan Mohamad @ Che Hashim - Mohamad @ Che Hashim, Che Adnan (1993)
This project work is concerned with study of the characteristic behavior of bonded Class III posttensioned rectangular simply supported beam using ultimate limit state design. Six specimens were prepared.They were reinforced, hyperbolic and straight tendon prestressed concrete beams. A couple of beams were tested under one point load at mid-span and two point load at one-third from supports. Cracking load, ultimate load, strain and crack propagation were observed and recorded during the testing. The experimental results were compared with the calculated and ANSYS (Analysis System) computer program. AN SYS computer program also was used in determining the actual modulus elasticity of concrete for each beam.